Nutritional status of Tajik children and women: Transition towards a double burden of malnutrition. Issue 2 (8th November 2019) - Barth‐Jaeggi, Tanja; Zandberg, Lizelle; Bahruddinov, Mutribjon; Kiefer, Sabine; Rahmarulloev, Sherali; Wyss, Kaspar
Abstract: The double burden of malnutrition, an emerging concern in developing countries, can exist at various levels: individual, household, and population. Here, we explore the nutritional status of Tajik women (15–49 years) and children (5–59 months) focusing on overweight/obesity along with undernutrition (underweight, stunting, and micronutrient deficiencies). For this, nutritional markers (haemoglobin (Hb), transferrin receptor (TfR), serum ferritin (Sf), retinol binding protein (RBP), vitamin D, serum folate, and urinary iodine), height, and weight were assessed from 2, 145 women and 2, 149 children. Dietary intake, weaning, and breastfeeding habits were recorded using a 24‐hr recall and a questionnaire. Overweight (24.5%) and obesity (13.0%) are increasing among Tajik women compared with previous national surveys (2003 and 2009). Prevalence of iron deficiency and anaemia was 38.0% and 25.8%, respectively; 64.5% of women were iodine deficient, 46.5% vitamin A deficient, and 20.5% had insufficient folate levels. Women in rural areas had significantly lower iron status and body mass index and higher iodine intake compared with urban areas; 20.9% of children were stunted, 2.8% wasted, 6.2% underweight, 52.4% iron deficient, and 25.8% anaemic; all more prominent in rural areas. Dietary diversity was higher among urban women. Intraindividual or household double burden was not seen. In summary, double burden of malnutrition constituted an increase in overweight among women, especially in urban areas, and persisting levels of undernutrition (stunting, iron, and vitamin A deficiency), predominately in rural areas. A holistic, innovative approach is needed to improve infant and young children feeding and advise mothers to maintain an adequate diet. Abstract : Rituximab was digested with immobilized pepsin and papain to yield F(ab')2 and Fab' fragments respectively. Fragments were conjugated with p‐SCN‐Bn‐NOTA and immunoconjugates labeled with Ga‐68. Specificity of radioimmunoconjugates was ascertained by cell binding and inhibition assays with unlabeled antibody.